Estimating Geweke's (1982) Measure of Instantaneous Feedback. (March 2013) - Dicle, Mehmet F.; Levendis, John
In this article, we describe thegwke82 command, which implements a measure of instantaneous feedback for two time series following Geweke (1982, Journal of the American Statistical Association 77: 304–313).